AN ANALYSIS OF ISLAMIC BOARDING SCHOOL STRATEGY IN EMPOWERING THE ECONOMY OF THE SOCIETY DURING COVID 19 PANDEMIC: A STUDY AT RAUDHATUL ULUM SAKATIGA ISLAMIC BOARDING SCHOOL, SOUTH SUMATERA - Abizar Abizar; Nina Ramadhani Wulandari; Ibnu Irawan (Kodifikasia: Jurnal Penelitian Islam, 2021)
Kondisi pandemi Covid-19 yang meluas saat ini mengancam dan berdampak pada perekonomian masyarakat kelas bawah. Dimana harga pangan naik dan permintaan pasar meningkat dalam skala nasional. Pesantren dengan kegiatan pendidikan dipandang mampu memberikan nafas dan kehidupan bagi masyarakat sekitar, sehingga perlu mengkajinya agar dapat memperoleh manfaat melalui suatu kajian. Masalah yang diteliti adalah; 1) eksplorasi program pemberdayaan ekonomi Pondok Pesantren Raudhatul Ulum sebagai potensi pemulihan ekonomi 2) relevansi prinsip-prinsip pemberdayaan ekonomi syariah dalam program pemberdayaan pemulihan ekonomi di Pondok Pesantren Raudhatul Ulum. Hasilnya adalah: 1) Program digulirkan; Wisata islami, penyediaan penginapan, laundry, pengadaan makanan, kerjasama penyediaan kantin, pelayanan outbond, penyediaan sarana olahraga berupa lapangan futsal dan gedung olah raga, pelaksanaan agribisnis, permodalan dan kerjasama di bidang pertanian, penyediaan air mineral. 2) Program-program tersebut relevan untuk dilaksanakan di lingkungan lembaga pendidikan sebagai pusat roda pemulihan ekonomi masyarakat di masa pandemi covid 19. Program ekonomi adalah program yang dilandasi nilai-nilai keadilan, mas'uliyah atau tanggung jawab, dan takaful, dengan tujuan program ekonomi adalah pemulihan ekonomi, ekonomi kelembagaan yang sehat, dan masyarakat yang sejahtera. Kata kunci: Pesantren; Pemberdayaan ekonomi; Covid-19 Abstract:The current condition of the widespread Covid-19 pandemic threatens and has an impact on the economy of the lower class. Where food prices rise and market demand increases on a national scale. Islamic boarding schools with educational activities are seen as being able to provide breath and life for the surrounding community, so it is necessary to study them in order to obtain the benefits through a study. The problems studied are; 1) exploration of the economic empowerment program of the Raudhatul Ulum Islamic Boarding School as a potential for economic recovery 2) the relevance of the principles of Islamic economic empowerment in the economic recovery empowerment program at the Raudhatul Ulum Islamic Boarding School. The results are: 1) The program is rolled out; Islamic tourism, provision of lodging, laundry, food procurement, cooperation in providing canteens, outbound services, provision of sports facilities in the form of futsal fields and sports halls, implementation of agribusiness, capital and cooperation in agriculture, provision of mineral water. 2) The programs is relevant to be implemented within educational institutions as the center of the community's economic recovery wheel during the covid 19 pandemic. The economic program is a program based on the values of justice, mas'uliyah or responsibility, and takaful, with the aim of the economic program being a recovering economy, a healthy institutional economy , and a prosperous society. Keywords: